Coloured light pollution in the urban environment - Kowalska, Justyna (Photonics Letters of Poland, 2019)
The article deals with issues related to colored lighting occurring in urban space. On the example of the Colosseum Amphitheatre 3D model, applications of colorful illumination were shown and the rationale for using color in individual cases was discussed. The aim of the article is to draw attention to proper planning and modernization of lighting to limit the negative interference of light in the ecosystem. Full Text: PDF References P. R. Boyce, "The benefits of light at night", Building and Environment, 151, 356-367 (2019) CrossRef Y. Hu,T. Zhang ,J. Chen, D. Ma ,C. Cheng, " Hybrid Organic Light-Emitting Diodes with Low Color-Temperature and High Efficiency for Physiologically- Friendly Night Illumination", Israel Journal of Chemistry, 54, 979-985 (2014) CrossRef W. Jernarczyk, "Dwa oblicza światła", Kosmos, 64, 625-632 (2015) DirectLink J.D.Bullough, M.S Mies, "The blue-light hazard:A review", Journal of the Illuminating Engineering Society,29, 6-14 (2013) CrossRef M. Rivas., P.T. Santidrian, J. U. Dieguez, A. Marco, " Leatherback hatchling sea-finding in response to artificial lighting:Interaction between wavelenght and moonlight", Journal of Experimental Marine Biology and Ecology, 463, 143-149 (2015) CrossRef S. Marcinkowska, E. Tęgowska, "Oddziaływanie światła o różnym spectrum na bezkręgowce zmierzchu I pełnego dnia", Kosmos, 64, 589-597 (2015) DirectLink P. Jakubowski, "Wpływ rozkładu widmowego mocy promienistej ulicznych opraw oświetleniowych typu LED na zanieczyszczenie światłem otoczenia", Kosmos, 64, 643-653 (2015) DirectLink K. Skarżyński, "Iluminacja obiektów architektonicznych a zanieczyszczenie środowiska światłem", Kosmos, 64, 553-562 (2015) DirectLink P. Tabaka, I. Fryc, "Zależność poziomu zanieczyszczenia otoczenia światłem od kształtu krzywej użytkowanej oprawy oświetleniowej", Kosmos, 64, 669-677 (2015) DirectLink W.Żagan, K.Skarżyński, "Analysis of light pollution from floodlighting: Is there a different approach to floodlighting?", Light and Engineering, 25, 75-82 (2017) DirectLink J.Kowalska, "Zanieczyszczenie światłem barwnym obrazu miast", Polish Journal for Sustainable Development, 21, 69-76 (2017) CrossRef C.Gardner, "The use and misuse of coloured lighting in the urban enviroment", Optics&Laser Technology, 38, 366-376 (2006) CrossRef